Effect of hypnotherapy on prolactin level in women after cesarean section - Supriyadi Hari Respati; Risang Bhaskoro; Eric Edwin Yuliantara; Uki Retno Budihastuti; Debree Septiawan (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundPostpartum depression occurs in women after cesarean section, due to increased cortisol and decreased prolactin levels, leading to delayed breast milk production. Hypnotherapy is one of the most effective and efficient complementary therapy options for reducing postpartum depression. Hypnotherapy increases oxytocin secretion from the paraventricular nucleus of the anterior pituitary gland, decreases cortisol levels, and increases prolactin, thereby increasing breast milk production. This study evaluates hypnotherapy’s effect on prolactin levels after a cesarean section. MethodsThis study was an experimental non-blinded randomized controlled trial with a post-test-only control group design conducted at Dr. Moewardi General Hospital and UNS hospital. A total of 20 post-cesarean -section women were included in the study. They were randomized into two groups, a group I: given hypnotherapy, and group 2: the control group (without hypnotherapy). Both groups were tested for prolactin levels. Group I received hypnotherapy 6 to 12 hours post-cesarean section, and study participants were confirmed to be unaffected by the anesthetic. Data analysis used the independent t-test and p<0.05. ResultsAt baseline, there was no significant difference in age, parity, and indication for cesarean section between the hypnotherapy and the control groups (p>0.05). After intervention, the mean prolactin level was higher in the hypnotherapy group (247.6 ± 81.1 ng/mL) compared to the control group (120.1 ± 55.4 ng/mL) (p<0.001). ConclusionHypnotherapy increases post-cesarean prolactin levels compared to the controls. Our findings open up a wide range of potential hypnotic applications among women with postpartum depression.